What is global excess liquidity, and does it matter? - Rasmus Rüffer; Livio Stracca (European Central Bank (ECB), 2006)
This paper endeavours to provide a comprehensive analysis of the nature and the possible importance of “global excess liquidity”, a concept which has attracted considerable attention in recent years. The contribution of this paper is threefold. First, we present some conceptual discussion on the meaning of excess liquidity in advanced countries with developed financial markets. Second, we report some descriptive analysis on the degree of co-movement of several possible measures of excess liquidity and spill-overs between them for a relatively large sample of industrialised and developing countries. Third, we estimate a VAR model for an aggregate of the major industrialised countries and analyse the transmission of shocks to global excess liquidity to the global economy, including possible cross-border spill-over effects to a number of domestic variables in the world's three largest economies (the US, the euro area and Japan).
Keywords: E52; F42; 330; Global excess liquidity; international economics; monetary policy; open economy; Währungsreserven; Geldpolitik; Offene Volkswirtschaft; Internationaler Finanzmarkt; Geldpolitische Transmission; Theorie; Industrieländer; Entwicklungsländer